1997
DOI: 10.1901/jaba.1997.30-459
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Client Preference for Function‐based Treatment Packages

Abstract: Functional communication training (FCT) and noncontingent reinforcement (NCR) are commonly prescribed treatments that are based on the results of a functional analysis. Both treatments involve delivery of the reinforcer that is responsible for the maintenance of destructive behavior. One major difference between the two treatment procedures is that client responding determines reinforcement delivery with FCT (e.g., reinforcement of communication is delivered on a fixed-ratio 1 schedule) but not with NCR (e.g.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
194
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 176 publications
(206 citation statements)
references
References 23 publications
11
194
1
Order By: Relevance
“…An objective model for addressing questions of efficacy and preference was originally described by Hanley, Piazza, Fisher, Contrucci, and Maglieri (1997) when attempting to identify treatments for the problem behavior of two young children with intellectual disabilities. After learning via functional analysis (Iwata et al, 1982(Iwata et al, /1994) that the two children's aggression and disruption were maintained by adult attention, two functionbased treatments were designed.…”
Section: Single-person Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An objective model for addressing questions of efficacy and preference was originally described by Hanley, Piazza, Fisher, Contrucci, and Maglieri (1997) when attempting to identify treatments for the problem behavior of two young children with intellectual disabilities. After learning via functional analysis (Iwata et al, 1982(Iwata et al, /1994) that the two children's aggression and disruption were maintained by adult attention, two functionbased treatments were designed.…”
Section: Single-person Applicationsmentioning
confidence: 99%
“…These results underscore the fact that if treatment options were restricted to those considered nonaversive or positive, the children in this study would have been prescribed treatments that were both ineffective and non-preferred. Taken together, the studies by Hanley et al (1997Hanley et al ( , 2005 suggest that the values guiding the selection of treatment strategies can be data-based. That is, treatment decisions need not be based on the name or structure of the intervention; they can be based on measures of efficacy and child preference.…”
Section: Single-person Applicationsmentioning
confidence: 99%
“…Each session was conducted using a modified concurrent-chains procedure (Hanley, Piazza, Fisher, Contrucci, & Maglieri, 1997). That is, each session was divided into two parts called initial and terminal links.…”
Section: Response Measurementmentioning
confidence: 99%
“…Hanley and colleagues, for example, recently compared the effectiveness of FCT with noncontingent reinforcement (NCR) on the multiple behavior problems of 2 children (Hanley, Piazza, Fisher, Contrucci, & Maglieri, 1997). They found that both interventions initially reduced problem behaviors, but that the participants demonstrated a preference for FCT.…”
Section: Mark Durand University At Albany State University Of Newmentioning
confidence: 99%